Reforms of the Banking Sector of the Republic of Uzbekistan - Eduardovna, Kim Elena; Mahomadrizoevna, Karimova Aziza (Research Parks Publishing LLC, 2023)
This article contains certain issues for consideration, and they are based on reforming the banking system, what it is, what measures have been taken to improve banking activities and how all this together has affected the banking sector of the Republic of Uzbekistan.